Analysis Of Internal Control And Internal Audit On Financial Performance Through Good Corporate Governance - Eny Lestari Widarni (Vifada Management and Social Sciences, 2025)
Purpose:This study aims to examine the effect of internal control and internal audit on financial performance, with Good Corporate Governance serving as a mediating variable, at PT. Pegadaian Malang Branch. Research Design and Methodology: A quantitative research design was employed, involving 73 respondents. Data were collected via questionnaires and analyzed using the Partial Least Square (PLS) method with SmartPLS 3.0 to test the relationships among the variables. Findings and Discussion: The results show that both internal control and internal audit have a positive and significant impact on financial performance. Additionally, Good Corporate Governance was found to mediate these relationships, enhancing the effect of internal control and internal audit on financial outcomes. These findings highlight the critical role of integrating governance practices and internal oversight to improve operational efficiency, financial reporting accuracy, and overall company profitability. Implications:This study provides practical insights for management to strengthen governance structures, enhance the effectiveness of internal supervision, and ensure sustainable financial performance and corporate reputation